Capacitive energy harvesting using soft dielectric elastomers : design, testing and impedance matching optimization - Wang, Yongquan (2018)
Energy harvesting based on dielectric elastomeric materials, in nature, embodies a capacitive kinetic energy conversion mechanism where the soft DE generator (DEG) interactively cooperates with conditioning circuits. Based on the principle of passive charge pump, this paper proposes a design concept for a self-cycling energy harvesting circuit driven by DEG cyclic deformation, with its essential behavioral mode laid on the electrical reciprocity between the DEG intrinsic capacitor and another capacitor connected in series. By detailed simulation experiments, the working process and dynamic characteristics of the proposed system, as well as the influence of circuital, operating, and load parameters on system performance are quantitatively investigated, with intensive discussions for the time delay behaviors caused by changes of load resistance, along with the different impacts of its value regions. Then, the theoretical analyses are effectively validated by experimental tests for a specially-designed annular DEG prototype. Under the global optimization framework based on impedance matching, this paper presents some guidelines for circuit design, e.g., the selection criteria of the capacitance and load resistance. In addition, the potential of this emerging technology is also demonstrated by experiments.